2017
DOI: 10.18203/2349-3291.ijcp20175579
|View full text |Cite
|
Sign up to set email alerts
|

Infant and young child feeding practices among mothers attending an Urban Health Training Centre (UHTC): a cross-sectional (mixed methodology) study in Berhampur, South Odisha, India

Abstract: Background: Adequate nutrition during infancy and early childhood is essential to ensure the health, growth and development of children. The objective of this study was to assess infant and young child feeding practice among mothers with 0-24 months children as per WHO criteria. Methods: It was a cross sectional study, involving mixed methodology (quantitative method supplemented by qualitative method in-depth interview) among 374 respondents from 1 st May 2017 to 31 st August 2017. Results: In quantitative me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
1
12
1
Order By: Relevance
“…[ 9 ] In qualitative study done by Karmee N et al in 2018 in Odisha also found that majority mothers started breastfeeding within an hour of delivery and exclusively breastfeed till 6 months, around one-third participants gave pre-lacteal feed to baby, most common pre-lacteal feed was honey usually given for prevention of infection. [ 10 ] Time for initiation of breast feeding was mostly immediate after the delivery of baby occurred to 2 hours after it. Geetalkshmi RG et al (2017) and Ahishakiye et al (2019) in their qualitative study also found that most of mothers start breasfeeding within 2 hours of delivery and pre-lacteal feed was avoided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ] In qualitative study done by Karmee N et al in 2018 in Odisha also found that majority mothers started breastfeeding within an hour of delivery and exclusively breastfeed till 6 months, around one-third participants gave pre-lacteal feed to baby, most common pre-lacteal feed was honey usually given for prevention of infection. [ 10 ] Time for initiation of breast feeding was mostly immediate after the delivery of baby occurred to 2 hours after it. Geetalkshmi RG et al (2017) and Ahishakiye et al (2019) in their qualitative study also found that most of mothers start breasfeeding within 2 hours of delivery and pre-lacteal feed was avoided.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to advertisement and implementation of BFHI and IYCF initiatives. [ 10 ] Another study in rural Nepal found only 2/3 rd of children initiated breastfeeding within an hour of birth though 90% of them was given colostrum. [ 5 ] Mothers had good knowledge and practice regarding the frequency and timing of breastfeeding as compared to the national figure of 43%.…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to the results of the study of Karmee et al where it was found to be 66.9% which may be because of the geographic proximity of the study areas. 6 However it was much higher than the results in the studies of Mondal et al where it was 30.85% and Chaudhary et al where it was 15.7%. 24,25 This may be due to the high rates of illiteracy among the mothers in these studies as compared to the current study.…”
Section: Discussionmentioning
confidence: 57%
“…5,3 Similar findings were reported by different authors wherein the value ranged from 81% to 88%. [6][7][8][9][10] This may be explained by the inclusion of tribal or backward class populations in these studies. It was much higher in studies conducted by Nisha et al where it was 98.6% and Madhu et al where it was 97%.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation